2019
DOI: 10.1177/2192568219886278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Expandable Versus Static Interbody Spacers via MIS LLIF: A 2-Year Radiographic and Clinical Outcomes Study

Abstract: Study Design: Retrospective cohort study. Objective: The purpose of this study is to compare the radiographic and clinical outcomes of expandable interbody spacers to static interbody spacers. Methods: This is a retrospective, institutional review board–exempt chart review of 62 consecutive patients diagnosed with degenerative disc disease who underwent minimally invasive spine surgery lateral lumbar interbody fusion (MIS LLIF) using static or expandable spacers. There were 27 patients treated with static spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Current literature reports LLIF fusion rates between 75–100%, which is similar to our study and those rates historically reported for ALIF, PLIF, and TLIF [23] , [24] , [25] , [26] . Ultimately, only 18 (21.95%) of our 82 patients were from the BSF analysis for not having follow-up imaging more than 6 months postoperatively, though reassuringly all of the patients who had reoperation or instrumentation complications were included in the analysis of BSF fusion scores.…”
Section: Discussionsupporting
confidence: 91%
“…Current literature reports LLIF fusion rates between 75–100%, which is similar to our study and those rates historically reported for ALIF, PLIF, and TLIF [23] , [24] , [25] , [26] . Ultimately, only 18 (21.95%) of our 82 patients were from the BSF analysis for not having follow-up imaging more than 6 months postoperatively, though reassuringly all of the patients who had reoperation or instrumentation complications were included in the analysis of BSF fusion scores.…”
Section: Discussionsupporting
confidence: 91%
“…With eLLIFp, back and leg pain improved over 90% by the time of solid fusion. These results were somewhat better than the 80% improvement reported for expandable lateral cages 14 and clearly superior to the 49% to 60% improvement with static cages. 4,8,13,19 Functional status and disability improved 47% and 69% in our cohort, which were similar to improvements reported for static cages but lower than that reported for expandable lateral cages.…”
Section: Discussionmentioning
confidence: 54%
“…4 disc height with less subsidence utilizing expandable lateral cages compared with impacted static lateral cages. [12][13][14] Expandable cages with lateral fixation significantly improved segmental stability and prevented anterior cage dislodgment. 15 Early experience using these expandable lateral titanium interbody cages with integrated lateral plate fixation (eLLIFp) found the device to be robust and not require supplemental posterior pedicle screw-rod fixation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Li et al compared the radiographic outcomes in 62 patients with degenerative disc disease after insertion of a static (n = 27) or expandable (n = 35) device through an LLIF. 10 In the expandable group, the segmental lordosis improved from baseline at all timepoints (6 weeks, 3 months, 6 months, 12 months, and 24 months) and increased by a mean of 23% by 24 months. In the static group, the segmental lordosis improved significantly from baseline only at 24 months and increased by a mean of 17%.…”
Section: Lumbar Lordosismentioning
confidence: 80%
“…These findings varied from those of Li et al, where they studied 62 consecutive patients treated with an expandable (n = 35) or a static (n = 25) lateral lumbar interbody device. 10 At 24 months postsurgery, the expandable group showed significantly greater improvements in VAS back and leg pain and ODI compared to the static group. These 2 studies suggest that patients who undergo LLIF with expandable interbody devices have equivalent if not better clinical outcomes compared to those who receive static devices.…”
Section: Patient-reported Outcomesmentioning
confidence: 84%